THE INFLUENCE OF TOMAN FISH (Channa micropeltes) EXTRACT ON THE NUMBER OF NEOVASCULAR IN DIABETES MELLITUS WOUND HEALING In Vivo Study on the Back of Male Wistar Rat (Rattus novergicus) - Alya Royyana; Amy Nindia Carabelly; Didit Aspriyanto (Dentino : Jurnal Kedokteran Gigi, 2018)
Background: Patients with diabetes mellitus (DM) have delayed wound healing. This happens becauseof the depletion of neovascular number. Neovascular plays an important role in wound healing by restoringblood flow to the wound area, so the new tissue gets enough oxygen and nutrition supply to proliferate. Tomanfish (Channamicropeltes) contains albumin that can increase and decrease the number of neovascular, so it’spotentially become an alternative medicine to accelerates wound healing in DM. Purpose: The aim of thisresearch to prove the effect of toman extract dose 16 ml/Kg BW rat orally on the number of neovascular inwound of diabetic wistar rats on the 4th,8th and 14th day. Materials and methods: This research used trueexperimental method with posttest only control group design. This research used 36 wistar rats which were thendivided into 9 groups, toman fish extract dose 16 ml/Kg BW of rat group, haruan fish extract dose 13,54 ml/KgBW of rat group and BR2 feed only group. Research result: The results of One Way-Anova and Post Hoc LeastSignificant Difference tests showed there was a significant difference between group of toman extract and groupof feed only, while on group of toman extract and group of haruan extract showed there was no significantdifference on 4th,8th and 14th day. The average value of toman extract-given group on 4th, 8thand 14th day were14,75. 7,5 and 6,75 respectively. Conclusion: Toman extract has effects which are increasing the number ofneovascular on 4th day and decreasing the number of neovascular on 8th and 14th day in wound healing withDM.